IMPLEMENTASI LEBIJAKAN PEKERJA ANAK MENURUT KONVENSI ILO - Jumaidi Nur (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
This paper is a review of children labour. Theory on children development and empirical experience are provided to discuss the topic. Children labour has received seriuous attention from ILO. The fact that children labor increase from year to year is the world issues. Mostly, labor children are available in the informal sectors where the salary is low, health and wealth insurance is trivial, and dangereous jobs are done. Ecocomic crisis that has impact on various social conflicts runs along the recent years and people try to obtain solutions to cope with the problems. Protection to save the children from the damage of generation has been done.